2021
DOI: 10.1093/dote/doab037
|View full text |Cite
|
Sign up to set email alerts
|

Screening for synchronous esophageal second primary tumors in patients with head and neck cancer

Abstract: Summary Patients with head and neck squamous cell carcinoma (HNSCC) have an increased risk of developing esophageal second primary tumors (ESPTs). We aimed to determine the incidence, stage, and outcome of synchronous ESPTs in patients with HNSCC in a Western population. We performed a prospective, observational, and cohort study. Patients diagnosed with HNSCC in the oropharynx, hypopharynx, any other sub-location in combination with alcohol abuse, or patients with two synchronous HNSCCs, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 26 publications
(49 reference statements)
2
23
0
Order By: Relevance
“…The expected incidence of 2 % to 10 % for synchronous ESPTs in this study is in line with that found in our previous screening study 17 . Our research group reported a 5.9 % (95 % confidence interval 1.9 %–13.2 %) incidence of ESPTs in 85 patients diagnosed with human papillomavirus-negative HNSCC located in the hypopharynx, oropharynx and other HN sublocations in patients with alcohol abuse in the Netherlands 17 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The expected incidence of 2 % to 10 % for synchronous ESPTs in this study is in line with that found in our previous screening study 17 . Our research group reported a 5.9 % (95 % confidence interval 1.9 %–13.2 %) incidence of ESPTs in 85 patients diagnosed with human papillomavirus-negative HNSCC located in the hypopharynx, oropharynx and other HN sublocations in patients with alcohol abuse in the Netherlands 17 .…”
Section: Discussionsupporting
confidence: 93%
“…Four of 10 medical specialists expected the prevalence of HNSPTs in ESCC patients and vice versa to be ≤ 3 % or ≥ 20 %. Median expectations of the prevalence of SPTs in ESCC and HNSCC patients of 5.0 % were comparable to numbers reported in recent studies [4,15,17]. Our research group performed a retrospective study with 9,058 ESCC patients in the Netherlands and found a 3.0 % prevalence of HNSPTs in patients with primary ESCC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the diagnostic sensitivity of NBI endoscopy (100.0%) was superior to whole body PET/CT (33.3%) in detecting esophageal SPTs ( 71 ). In a review of 14 studies with 2,743 HN cancer patients, IEE screening identified esophageal high grade dysplasia or invasive carcinoma in 13% (95% CI, 9-19% with a random effects model) of the patients ( Table 2 , Figure 3 ) ( 8 , 10 12 , 70 – 79 ). Most of the esophageal SPTs were at an early stage without tumor-related obstructive symptoms.…”
Section: Image-enhanced Endoscopic Screening and Risk Factors For Eso...mentioning
confidence: 99%